Letters of Sultan Salah al-Din al-Ayyubi to the Caliph al-Mansur al-Mowahidi and his position on it - عباس, رندة; الشدود, عامر غسان (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study of diplomatic relations in the Middle Ages requires a definition of diplomacy and its goal, as diplomacy is as old as human groups, and it is a natural reflection of the movement of these groups, and in their interactions with each other, which aims to control the relations between them, and diplomacy has been characterized in every stage that has passed. With new features that revealed its features and fields. However, the diplomatic reality in ancient and medieval times was distinguished by its being temporary and bilateral diplomatic missions, which ended with the end of the visit's goal of accepting or rejecting the ideas of the envoy, and with the weakness of the Abbasid Empire and its division into a group of kingdoms and Emirates, and the external ambitions that accompanied it represented by the Crusades, where Diplomatic activity flourished between those kingdoms and emirates, which played a key role in confronting these hostile forces, through cooperation between them and agreement with each other to limit the impact of these campaigns on the political, economic and demographic reality of the region in general and the Arab Levant in particular.